Speech Acts Performed by Voldemort within the Movie “Harry Potter: The Deathly Hollows Part I”: Types and Translation Strategies - Khaeriyah; Ani Maghfiroh (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2023)
This research investigates what types of speech acts that Voldemort used and the procedures applied in translating its subtitle in movie “Harry Potter: The Deathly Hollows Part 1”. Descriptive qualitative analysis was set up as the method whilst the theories of Yule (1996) and Vinay & Darbelnet (1958) were used as the main roadmap to analyze the data. The researcher collected data by employing a note-taking technique and gaining the data by searching, downloading, watching the movie, taking notes and marking its transcript in its dialogue. In analyzing data, the researcher used the content analysis technique and the steps are by searching, identifying, classifying them according to the speech acts theory of Yule (1996). As the result, 67 speech acts performed by Voldemort were discovered such as; declarative, representative, expressive, commissive, and directive. Meanwhile, the directive speech act was dominantly used (29 data). On the other hands, it was encountered that a number of translation procedures were applied. They are literal translation, pure borrowing, modulation, generalization, adaptation, addition, deletion while literal translation dominates (42 data).